Precipitated calcium carbonate modified by the layer-by-layer deposition method - its potential as papermaking filler - Lourenço, A. F. (2015)
The surface modification of papermaking fillers with compounds that promote a better bonding with the cellulosic fibres is nowadays one of the strategies used to increase the filler content in paper without sacrificing the mechanical properties. In this study precipitated calcium carbonate (PCC) was surface coated with poly(diallyldimethylammonium) using the layer-by-layer deposition method with alginate as an intermediate bonding polyelectrolyte. The deposition of small amounts of both polyelectrolytes at the surface of PCC was confirmed by different techniques, namely by zeta potential measurements and X-ray photoelectron spectroscopy. The filler particles coated with two layers (one layer of each polyelectrolyte) and with six layers (three alternating layers of each anionic and cationic polyelectrolyte) were used in laboratory papermaking tests. It was observed that the handsheets mechanical resistances were better with the six-layer coated PCC than with the reference PCC whereas the optical properties were not significantly affected. It is therefore possible to increase the filler content in paper using a new PCC-based filler obtained by a cheap and simple modification method.